Need for Supreme Prominence to the Development of Railways - Brar, B. S.; Brar, A. P. K. (Asian Review of Mechanical Engineering, 2016)
There is need to facilitate the enhancement of capacity in human-beings to develop pro-people and pronational technologies, production-systems, and management models. In our country, there should be more stress on promotion of labour-intensive enterprises so as to increase the employment opportunities and to solve the wide-spread and serious problem of unemployment. The nature and direction of our industrial production should be to fulfill real national and peoples’ needs. The technologies should be such that these utilise and develop local resources and expertise. This will certainly facilitate our movement on the path of having and establishing the self-reliance in our country. To satisfy all the necessities, production-processes are necessary. For this, development of productive-forces (means of production plus human-resources) is a must. To develop productive-forces, the development of productive-relations is also necessary. Development of productive-forces and productive-relations is what constitutes the development of economic-base of the country. Infra-structure is necessary for economic development of the nation. Transportation is an important aspect of infra-structure. The development of transportation is vital not only for economic development of the country and the people, but also for the development of the country and the people in social and cultural spheres. There are four basic modes of transport viz. roadways, railways, waterways, and airways. Every mode of transport has relative advantages and disadvantages. In case of waterways and airways, the vehicle and load has to move through fluids. In case of fluids, there is viscous dragging force due to viscosity of the fluid which is infact internal-fraction between layers of the moving fluid. It is quantified by concept of co-efficient of viscosity. Whenever a small spherical body moves through a viscous fluid, then layers of the fluid which touch the body, are dragged along with the body, while the layers of the fluid away from the body remain at rest. Hence a relative motion between different layers of the fluid is developed. As a result, a backward dragging force comes into play. This viscous-dragging force is in addition to the viscous-drag which is inherent in the fluid motion. Moreover, when a body moves through the fluid, then there is also the presence of external-friction between the surface of the body and the “surface” of the fluid taking fluid as a bulk quantity. Therefore, when a body moves through a fluid, then the body has to struggle against three opposing forces: viscousdragging force inherent in the fluid, viscous-dragging force due to the motion of the body through the fluid, viscousdragging force due to external friction (air-friction), and all these three opposing forces reinforce one-another to become a formidable opposing force. Role of viscosity concerning motion of fluids is more determined by a relatively new concept of “Kinematic Viscosity” rather than the concept “Co-efficient of Viscosity”. We see that kinematic viscosity for air is greater than that of water, so more power will be required for the vehicle and the load to move through air than through water. It is a commonestimation that the energy requirement to carry unit load per unit distance in case of railways is one-fourth to one-sixth of the energy requirement for roadways. The basic point is that co-efficient of friction between steel-and-steel surfaces in case of railways is far less than co-efficient of friction between rubber-and-concrete surfaces. In case of railways and roadways, the role of the phenomenon of elasticity is also important. Hooke’s Law states that within elastic limit, the extension produced in a wire is directly proportional to the load applied. Co-efficient of elasticity or modulus of elasticity of the material of the body is the ratio of the stress and the corresponding strain produced, within elastic limit. All the three kinds of modulus of elasticity of steel are large, also it has other good properties like being flexible and being comparatively cheap. Also co-efficient of friction for steel-steel surfaces is small. These factors combined lead to the selection of steel in railways. Of the modes of transportation of roadways and railways, supreme stress should be on the development of railways, as less force is required to move trains, leading to less use of petroleum products, so the most economical. Also, less pollution of the environment will be there.